How Transformational Leadership, Corporate Culture, and Intrinsic Motivation Shape Hospitality Employee Performance? - Anshori, Mohamad Yusak; Rasyid, Reizano Amri; Herlambang, Teguh (Universitas Airlangga, 2025)
Objective: Guided by Self-Determination Theory (SDT), this study investigates the effects of transformational leadership, corporate culture, and company values on intrinsic motivation and employee performance in the hospitality industry. Design/Methods/Approach: Data were collected from 277 hotel employees across multiple departments using structured surveys. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to assess both direct and indirect effects among the variables. Findings: The results demonstrate that transformational leadership, corporate culture, and company values have a significant influence on intrinsic motivation, which in turn enhances employee performance. Intrinsic motivation acts as a key mediating mechanism linking organizational factors to performance outcomes. A strong organizational culture and value congruence emerge as critical drivers of employee motivation and effectiveness in the hospitality context. Originality/Value: This study contributes to the organizational behavior and human resource management literature by integrating multiple theoretical perspectives (SDT, Person–Organization Fit, and Full-Range Leadership Theory) into a unified model. The application of PLS-SEM provides robust insights into the psychological mechanisms that shape performance, particularly within service-intensive environments such as the hospitality sector. Practical/Policy implication: The study offers actionable insights for hospitality managers, including the design of leadership development programs, embedding organizational values into operational routines, and fostering cultures that meet employees' psychological needs. These interventions are essential for sustaining engagement and performance in dynamic service settings.